Do Reading Comprehension, Verbal Working Memory and Visual-Spatial Working Memory Predict Borderline Intellectual Functioning in English Language Learners? - Nitz, Jonathan (ProQuest Dissertations & Theses, 2022)
The purpose of this study is to add more information to what is known about nonbiased means of measuring borderline intellectual functioning in English language learners whose first language is Spanish. A lack of studies showing the ability to appropriately identify English language learners with borderline intellectual functioning guided the complete dissertation research. The research added to what is known about working memory’s ability to predict student with borderline intellectual functioning (SS < 80) or with low average to average intellectual functioning (SS ≥80). A logistical regression analysis showed the ability of reading comprehension, verbal working memory and visual-spatial working memory to predict full scale IQ. This ex post facto analysis was conducted on the records of English language learners, ages 6-14, with a first language of Spanish. Regarding the individual constructs as predictors, visual-spatial working memory was a significant predictor that added the most power to the model. Reading comprehension also significantly added to the model. Verbal working memory was not a significant predictor. The highest predictive power came from the combination of visual-spatial working memory and reading comprehension. As this research was ex post facto there are several limitations to the generalizability of this research, but it does indicate that this may be the first step in a line of further research.